2015
DOI: 10.1177/1071100715593374
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Acute Superficial Deltoid Complex Avulsion During Ankle Fracture Fixation in National Football League Players

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 21 publications
0
58
1
1
Order By: Relevance
“…However, some recent and well-done studies suggested a better outcome after DL repair [15-17, 26, 27]. Hsu et al [27], in his series of 14 National Football League (NFL) players with ankle fractures, found that open DL repair allowed return to play with no complications at 12-month follow-up. In another study by Yu et al [26], DL repair in 106 patients with acute ankle fractures resulted in satisfactory functional outcomes, with no clinical or radiological evidence of post-traumatic ankle arthritis in fractures managed with DL repair, as observed at an average of 27-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, some recent and well-done studies suggested a better outcome after DL repair [15-17, 26, 27]. Hsu et al [27], in his series of 14 National Football League (NFL) players with ankle fractures, found that open DL repair allowed return to play with no complications at 12-month follow-up. In another study by Yu et al [26], DL repair in 106 patients with acute ankle fractures resulted in satisfactory functional outcomes, with no clinical or radiological evidence of post-traumatic ankle arthritis in fractures managed with DL repair, as observed at an average of 27-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous ligament reconstruction techniques have been proposed; however, clear indications for operative repair have not yet been well established. Some studies have shown that repair of the ruptured ligament is beneficial and can produce satisfactory results [11,12,14,20]. By contrast, other studies showed repair of the deltoid ligament to be unnecessary [1,4,10,17,21].…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports in terms of detailed biomechanics of the deltoid ligament [11,16,18,19,20], and no reports have measured the biomechanics of each ligamentous band, due to the difficulty in inserting sensors into the narrow ligaments. The paucity of biomechanics data regarding each ligamentous band may have contributed to less reliable results of secondary repairs or reconstructions of the deltoid ligament.…”
Section: Introductionmentioning
confidence: 99%
“…Metitiri et al (21) destacaram os altos graus de erro e imprecisão nas medições, o que poderia ser uma desvantagem e limitação para o teste de estresse manual na detecção de instabilidade. A artroscopia relatada para avaliação da lesão do DL pode ser considerada uma alternativa válida (19,22,23) .…”
Section: Discussionunclassified